The uptake of the Prepex and Shang ring male circumcision devices among adolescent and adult males in Africa, a systematic review - Rajab, Kakaire Menyha (Department of Public Health and Family Medicine, 2019)
Voluntary medical male circumcision (VMMC) programs have been implemented in fourteen countries in sub Saharan Africa since 2007. The uptake of services has been suboptimal in some of the countries partly due to the widespread use of surgical methods. Circumcision using device methods was postulated to increase the uptake of VMMC services by making the procedure quicker and more appealing to men. We conducted a systematic review to establish the uptake and acceptability of the Prepex and Shang ring male circumcision devices in VMMC program countries. A metaanalysis was also performed. Methods: A comprehensive literature search from several databases was carried out to identify studies reporting VMCC coverage, uptake or acceptability of either the Prepex or Shang ring device methods. Search terms included, “non-surgical methods, male circumcision instrumentation as well as the individual device names such as Prepex, Shang ring, Gomco, Mogen, Plastibell, Accucirc, Alisklamp, Ismail Clamp, Tara Klamp, Unicirc, Smartclamp”. Electronic searches were complemented by going through the reference lists of the included studies. All searches were carried out on 12th May, 2017. Included studies must have been conducted between 1st April, 2007 and 28th February, 2017.The search was limited to studies among adolescents and adults in VMMC implementing countries. Two reviewers independently reviewed, rated, and abstracted data from each article. Uptake estimates were pooled in a meta-analysis and stratified according to the device method and participant age using Stata. Acceptability of device methods among recipients was summarized using four criteria and presented as proportions. Results: Of the 391 total articles retrieved, 25 studies incorporating observational and interventional study designs met the inclusion criteria. Of these 25 studies, 7 articles reported uptake of device method, 5 and 2 being on the Prepex and Shang ring devices respectively. The pooled uptake estimate was 75% (95% confidence interval 62% to 89%). Prepex uptake was estimated to be 73% while the Shang ring estimates were 82%. On stratification by population group, uptake of device methods among adolescents was 82% compared to 72% by adults. Majority (21) of the studies reported at least one of the criteria used to assess device acceptability. Acceptability of the two device methods was high: 95% of participants reported satisfaction with a device procedure. The devices were not associated with lengthy periods out of work, with 87% of participants reported to have resumed normal activities within two days after the procedure. Almost all (97%) participants circumcised with the device methods indicated they would recommend a device procedure to a friend or relative. Conclusion: Our findings showed a high uptake and acceptability of the two circumcision devices methods that have been prequalified by WHO for use among adolescents and adults. There is a dearth of evidence on the extent of utilization of devices for adolescent or adult circumcision and whether this has improved the overall uptake of VMMC services, thus emphasizing the need for more studies on this topic.